THE EFFECT OF USING THINK PAIR SHARE TECHNIQUE TO DEVELOP STUDENTS’ READING SKILLS AT VIII GRADE OF SMP NEGERI 2 KOTA JAMBI - Karim Karim; Yanti Ismiyati (Universitas Batanghari Jambi, 2019)
The objectives of the research are to how the effectiveness of Think Pair Share to teach reading comprehension. The method used in this research was Think Pair Share technique. The subject of the research is the eighth grade students of SMP Negeri 2 Kota Jambi. There are 36 students of the eighth class E, and 36 students of the eighth class F. The conclusion in this research is a significant difference of the effects on the students’ reading comprehension between those who were taught using Think Pair Share and those who were taught without using think Pair Share. It can be proved from the score result of Null hypothesis (Ho) is accepted if the value of t-test is the same or less than the value of t-table ( t-test = t-table or t-test < t-table). In the fact, in this research, the null hypothesis is rejected because the value of t-test is higher than the value of t-table (5.437 > 2.032). Alternative hypothesis (Ha) is accepted if the value of t-test is higher than the value of t-table (t-test > t-table). Thus, the alternative hypothesis is accepted, the value of t-test is higher than the value of t-table (5.437 > 2.028. Based on the calculation analysis, it was found that there is improvement score on the students who were taught by think pair share technique. This can be seen from pre test result treatment and post test result after treatment.